INTEGRATING MEDIA-AND-MATERIAL DEVELOPMENT TASKS INTO ANEXTENSIVE READING CLASS - Siti Muniroh (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This article describes the integration of media-and-material development tasks in an Extensive Reading: Folk & Fairy Talescourse. Fifty-eight students were instructed to write reflection from their experience in performing reading and media-and-material development tasks. The results revealed that practical application of teaching reading by using materials for young learners was the most important thing they learned from the class. Moreover, most of the students reported that their creativity in media and material development, skills of story telling, and summarizing had been rehearsed while performing the tasks. Also, the tasks of reading and media-and-material development worked well for most of them; nevertheless, some students viewed making caterpillar as an excessive task. Meanwhile, the issues raised from the students were mostly about standard of scoring, act upon plagiarism, and their unhappiness on the caterpillar task. Thus, clear description of assessment and omission of caterpillar task were suggested for future practice